2009
DOI: 10.1074/jbc.m109.066712
|View full text |Cite
|
Sign up to set email alerts
|

Histidine 379 of Human Laeverin/Aminopeptidase Q, a Nonconserved Residue within the Exopeptidase Motif, Defines Its Distinctive Enzymatic Properties

Abstract: Human laeverin/aminopeptidase Q (LVRN/APQ) is a novel member of the M1 family of zinc aminopeptidases and is specifically expressed on the cell surface of human extravillous trophoblasts. Multiple sequence alignment of human M1 aminopeptidase revealed that the first Gly residue within the conserved exopeptidase motif of the M1 family, GXMEN motif, is uniquely substituted for His in human LVRN/APQ. In this study, we evaluated the roles of nonconserved His 379 , comprising the exopeptidase motif in the enzymatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Members of the M1 family of aminopeptidases share a common peptide-binding site (GXMEN) and peptidase activity motif (HEXXHX18E). Primate laeverin has a unique peptide-binding motif (HXMEN) where the first glycine (Gly) residue is substituted with histidine (His) [143], inducing significant changes in substrate specificity toward natural peptide hormones [144]. Laeverin is specifically expressed on EVT in the placenta from early and term pregnancy.…”
Section: Regulation Of Extravillous Trophoblast (Evt) Invasion By Embmentioning
confidence: 99%
“…Members of the M1 family of aminopeptidases share a common peptide-binding site (GXMEN) and peptidase activity motif (HEXXHX18E). Primate laeverin has a unique peptide-binding motif (HXMEN) where the first glycine (Gly) residue is substituted with histidine (His) [143], inducing significant changes in substrate specificity toward natural peptide hormones [144]. Laeverin is specifically expressed on EVT in the placenta from early and term pregnancy.…”
Section: Regulation Of Extravillous Trophoblast (Evt) Invasion By Embmentioning
confidence: 99%
“…Figure A shows a phylogenetic tree of the M1 family of human aminopeptidases based on their amino acid sequence identities. Twelve proteins belonging to the family have been identified in the human genome, and their enzymatic properties have been characterized. , It seems that APB, LTA4H, and RNPEP-L1 (arginyl aminopeptidase-like 1) comprise a distinct subfamily together with APO and PSA. ,, To identify whether there was a single residue responsible for the unique characteristics and enzymatic activity of APB, we compared the amino acid sequences of M1 aminopeptidases around the GXMEN motif (Figure B). As expected, alignment of M1 aminopeptidases around this motif indicated that APB has a sequence highly identical with those of LTA4H and RNPEP-L1, whereas it is less similar to other M1 aminopeptidases.…”
Section: Resultsmentioning
confidence: 99%
“…The consensus peptide recognition sequence of LVRN aminopeptidase is HXMEN. In rodents, Histidine has been substituted with Glycine and altered LVRN’s substrate specificity [27]. Moreover while human LVRN is specifically expressed in extravillous trophoblast [12], Lvrn mRNA was ubiquitously detected in mice (Fig.…”
Section: Discussionmentioning
confidence: 99%